Маркетологи на ринку праці: проблеми підготовки та професійної адаптації - Хтей, Н. І.; Дриль, О. І.; Земляк, І. Я. (Видавництво Львівської політехніки, 2012)
Проаналізовано тенденції затребуваності молодих фахівців окремих напрямів підготовки, попит на маркетологів, що сформувався на ринку праці. Визначено значення професії промоутера для формування майбутнього маркетолога, труднощі професійної адаптації молодих фахівців економічного профілю у новому колективі та умови і чинники, необхідні для цього. Проведене дослідження дало змогу визначити актуальність маркетингу як спеціальності, яка сприяє швидкому кар’єрному зростанню та роботи промоутером, що є першою сходинкою у формуванні кар’єри маркетолога. To the article a tendency is driven in relation to highly sought of young specialists of separate directions of preparation, demand on marketing specialists, that was formed at the market of labour, is analysed. The value of profession of promoter is analysed for a future marketing specialist. Difficulties over of professional adaptation of young specialists of economic profile and condition and factors necessary for professional adaptation of young workers in a new collective are brought. Undertaken a study gave an opportunity to do the row of conclusions in relation to actuality of marketing as speciality, that assists a rapid quarry increase and working as a promoter that is the first step in forming of career of marketing specialist.
Marketing specialists at the market of labour: problems of preparation and professional adaptation
Keywords: маркетинг; промоутер; професійна адаптація працівників; практична підготовка маркетологів; marketing; promoter; professional adaptation of workers; practical preparation of marketing specialists